The Varied Nature of the Dual Enrollment Student Experience - Courtney Adkins; Patrick Manapat; Linda García; E. Michael Bohlig (Educational Considerations, 2025)
Dual enrollment—a program in which high school students take college classes, earning credit for both—is growing at a rapid pace across America’s high schools and community colleges. While dual enrollment can help students fulfill high school graduation requirements and simultaneously make progress toward a postsecondary degree, some student populations are more likely than others to participate. Further, not all students who participate in dual enrollment find long-term success at the postsecondary level. To ensure better access and produce better outcomes for all students, it is critical to understand students’ experiences. In doing so, educational leaders will be able to identify the supports that are needed to successfully assist these students—especially those from historically underserved populations—and help them persist with their postsecondary education endeavors after earning a diploma. This article explores the findings of the first pilot administration of the Dual Enrollment Survey of Student Engagement (DESSE) and highlights differences in the dual enrollment student experience based on student characteristics, location of courses, and instructor type.
Keywords: Dual Enrollment; Student Experience; Location; Instruction; Student Characteristics